Comparative analysis of green finance policies in the EU, China and ASEAN: Policy implications for Vietnam - Nghiem Xuan Khoat, (Journal of Forestry Science and Technology, 2025)
This paper conducts a comparative analysis of green finance policies in the European Union (EU), China, and the Association of Southeast Asian Nations (ASEAN), aiming to draw relevant policy implications for Vietnam in the context of green transition. By examining legal frameworks, incentive mechanisms, financial instruments, and private sector involvement, the study reveals that each region follows a distinct approach. The EU stands out for its comprehensive legal architecture, including the EU Taxonomy for sustainable activities and stringent environmental, social, and governance (ESG) disclosure requirements. China adopts a state-led green finance model, with a strong policy push and oversight by the People’s Bank of China, combining regulatory incentives and financial guidance. ASEAN, meanwhile, is in a formative stage of policy development, focusing on harmonizing green standards, promoting regional green bond markets, and enhancing cross-border cooperation. Based on these insights, the paper proposes strategic recommendations for Vietnam, including the development of a robust legal framework for green finance, the establishment of a national taxonomy aligned with domestic priorities, and the strengthening of financial institutions and regulatory capacities. In addition, the paper emphasizes the need to incentivize private sector participation and create an efficient green capital market. The findings contribute significantly to Vietnam’s efforts in building a resilient green finance ecosystem that supports long-term sustainable growth. This study offers valuable guidance for policymakers, regulators, and financial actors engaged in the green transition.